Percutaneous transluminal angioplasty in arteriosclerotic internal carotid artery stenosis. - Bockenheimer, S A; Mathias, K (American Journal of Neuroradiology, 1983)
Percutaneous transluminal angioplasty (PTA) of carotid arteries has been rarely reported. Dilatation of internal carotid artery stenosis has so far been performed only for fibromuscular dysplasia. Because of the risk of cerebral embolization the technique has not been used for arteriosclerotic stenosis, particularly since endarterectomy is known as a safe procedure. Three cases are reported of successful dilatation of arteriosclerotic internal carotid artery stenosis. A neurologic complication occurred in one patient. The primary indication for performing PTA in such cases is limited operability for medical reasons.